Perceptually Based Approach for Planar Shape Morphing - Liu, Ligang; Wang1y, Guopu; Zhang, Bruce; Guo, Baining; Shum, Heung-Yeung (Institute of Electrical and Electronics Engineers, Inc., 2004)
This paper presents a novel approach for establishing vertex correspondences between two planar shapes. Correspondences are established between the perceptual feature points extracted from both source and target shapes. A similarity metric between two feature points is defined using the intrinsic properties of their local neighborhoods. The optimal correspondence is found by an efficient dynamic programming technique. Our approach treats shape noise by allowing discarding small feature points, which introduces skips in the traversal of the dynamic programming graph. Our method is fast, feature preserving, and invariant to geometric transformations. We demonstrate the superiority of our approach over other approaches by experimental results.